Selectivity and timing abilities of international socially responsible funds - Leite, Paulo (2014)
This article analyses the selectivity and market timing abilities of international Socially Responsible Investment (SRI) funds, from eight European markets, in comparison to conventional funds with similar characteristics. The results show that differences in market timing abilities of international SRI funds and their conventional peers are not statistically significant. However, SRI funds investing in European equities are significantly worse stock pickers than conventional funds, whereas for funds investing globally, selectivity abilities are similar among both fund groups. Hence, our results suggest that a broader investment universe might increase SRI fund managers’ stock picking abilities and, consequently, improve SRI fund performance.